Proses Produksi Program Acara Televisi Ketuk Pintu di Salam TV - Ja’far Ja’far; Azbar Rifa’i; Ali Akbar Siregar; Mahadir Muhammad (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
This research discusses the production process of the television program "Tap the Door" at Salam TV. The program aims to help underprivileged and needy individuals, as well as provide emotional support to them. Salam TV, as a da'wah television station, uses this program as a medium to educate the public about social issues and encourage active participation in helping those in need. This research uses a descriptive qualitative method with interviews, document review, and literature sources as data collection techniques. The informant interviewed was the producer of the Tap Pintu program. The research was conducted at Salam TV, North Sumatra. The production process of this event program consists of three stages, namely pre-production, production, and post-production. This research concludes that the production process of the "Ketuk Pintu" event program involves pre-production preparation, production activities such as shooting and interviewing, as well as the post-production stage which includes editing and airing. This research provides an overview of the production process of television programs with a focus on the "Ketuk Pintu" program at Salam TV.